Quantifying the linkages among agricultural, manufacturing and service sectors associated with GDP growth in Thailand - Pipitpojanakarn V. (2017)
© Serials Publications Pvt. Ltd. This paper analyzes the linkages among three economic sectors in Thailand, namely manufacturing, agricultural, and service sectors, as well as their contributions to Thailand's GDP growth using the quantile vector autoregression (QVAR) model. We have a special concern about a variety of distributions across quantiles and propose the multivariate skewed distributions for the QVAR model. Our empirical results find that service sector plays a crucial role to support other economic sectors while the impacts of the manufacturing and agricultural sectors turn out to be negative on the service sector. In addition, this analysis finds that during the expansion phrase, the manufacturing and service sectors play a significant role in boosting up the Thai economy. But in the recession, the service sector is the only significant engine that remains and drives the economy.